Highly efficient preparation of ZnO nanorods decorated reduced graphene oxide nanocomposites - Huang, N.M.; Marlinda, A.R.; Muhamad, M.R.; An'amt, M.N.; Chang, B.Y.S.; Yusoff, N.; Harrison, I.; Lim, H.N.; Chia, C.H.; Kumar, S.V. (2012)
A one-step method for the synthesis of zinc oxide/reduced graphene oxide (ZnO/rGO) nanocomposites by a hydrothermal technique is reported. This simple method involves a hydrothermal treatment of a solution comprising graphene oxide (GO), Zn(CH3COO)(2)center dot 2H(2)O, NaOH and NH3 center dot H2O. The concentration of GO as a starting material plays an important role in the density distribution of ZnO nanorods on the rGO sheets and on the percentage of the formation of ZnO/rGO nanocomposites. The resulting rod-like ZnO nanoparticles formed on the rGO sheets, in high density, has a potential in the gas sensing application. (C) 2012 Elsevier B.V. All rights reserved.